Repurposing dapagliflozin for Alzheimer's disease: a mechanistic exploration - Marwa M. Saeed (Future Journal of Pharmaceutical Sciences)
Abstract Background Several researches describe Alzheimer’s disease (AD) as Type-III diabetes mellitus due to shared pathophysiological mechanisms between AD and DM and the fact that one disease can increase the incidence of the other. Therefore, keeping glucose level under control protects the brain from its harmful effects and delays the incidence of AD in susceptible individuals by using anti-diabetic agents. Several anti-diabetic classes were explored for their protective effect against AD, among them that attracted more attention was sodium–glucose cotransporter inhibitor dapagliflozin (DAPA). Main body of the abstract This review aims at illustrating various protective mechanisms that DAPA proved to exert on cognition and memory. DAPA showed promising results by its influence on behavioral parameters highlighted enhancement of both spatial and non-spatial learning and memory, in addition to ameliorating associated anxiety by its effect on various neurotransmitters. DAPA succeeded in promoting neurogenesis, synaptic plasticity, and synaptic density, and managed to demonstrate anti-inflammatory, antioxidant, and antiapoptotic properties. Moreover, DAPA enhanced the activity of mitochondria and promoted autophagy, in addition to its impact on the PI3K/AKT/mTOR and Wnt/β-catenin signaling pathways. Short conclusion DAPA showed promising results in different AD models to enhance memory and improve cognitive deficits. Graphical abstract